POTENSI EKSTRAK DAUN Sphagneticola trilobataSEBAGAI INSEKTISIDA NABATI UNTUK MENGENDALIKAN LARVA Spodoptera litura - Efrin Firmansyah; Syafina Pusparani (Musamus Journal of Agrotechnology Research, 2019)
ABSTRACT The aim of this research was to study the potential of Sphagneticola trilobata as botanical insecticide to control Spodoptera litura larvae. The research consisted of several stages, namely insect rearing, plant extraction, bioassay, and phytochemical analysis. The results showed that the extract of Sphagneticola trilobata leaves caused mortality of S. litura larvae with the highest mortality of 72% at 5% concentration level. At the same concentration, the treatment caused the highest level of feeding inhibition was 76.12%. Phytochemical analysis results showed that S. trilobata leaf extract contained several secondary metabolite compounds including alkaloids, saponins, steroids, flavonoids and tannins. Keywords: Sphagneticola trilobata, Vegetable Insecticide, Weed